APLIKASI TASAWUF PADA DUNIA PENDIDIKAN DI ERA DISRUPSI (Telaah Kitab Siraj Al- Thalibin Karya Syeh Ihsan Jampes) - Muchasan, Ali; Naufal, Moh. (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2025)
Abstract: In the Qur'an, the term tasawuf is not explicitly mentioned. However, in substance, teachings related to tasawuf are implied within its verses. Etymologically, tasawuf is understood as a doctrine emphasizing self-purification and the closeness of a servant to the Most Holy. Education, on the other hand, can be defined as a conscious and planned effort to shape individuals into mature personalities, both in thought and action. In the modern era, many parents prioritize enrolling their children in educational institutions that focus on material success, such as securing stable jobs, while often neglecting the importance of character maturity and virtuous behavior. In this context, tasawuf emerges as a solution to balance worldly and spiritual needs. The success of education is not merely measured by how well graduates secure employment but also by their ability to develop mature thinking, strong character, and supportive skills. Although historically tasawuf has often been regarded as a cause of Islam's decline due to its perceived emphasis on the afterlife while neglecting worldly matters, this perspective warrants re-evaluation. In essence, the concept of tasawuf aligns with the Qur'anic values that emphasize a balance between worldly life and the afterlife, even though the term itself is not explicitly mentioned in the sacred text.